2006
DOI: 10.1038/modpathol.3800664
|View full text |Cite
|
Sign up to set email alerts
|

Solid pseudopapillary neoplasms of the pancreas are associated with FLI-1 expression, but not with EWS/FLI-1 translocation

Abstract: Solid pseudopapillary neoplasms of the pancreas are rare pancreatic tumors with mostly benign behavior, affecting almost exclusively women. Their histogenetic origin is still unsolved, but a recently reported EWS/FLI-1 translocation t(11;22)(q24;q21) and the consistent expression of CD56 and the progesterone receptor, both genes located on the long arm of chromosome 11, point to chromosome 11q as a potential locus of gene aberration in solid pseudopapillary neoplasms. To further elucidate this issue, we studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
19
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 15 publications
1
19
0
Order By: Relevance
“…One study of 30 solid pseudopapillary neoplasms and an additional case report did not show any chromosomal loss or gain. 11,17 Interestingly, all these cases had benign features. Using the more sensitive array CGH method, a recent report demonstrated loss of heterozygosity for HRAS in chromosome band 11p15.5 and a less significant loss of the short arm of chromosome 16.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…One study of 30 solid pseudopapillary neoplasms and an additional case report did not show any chromosomal loss or gain. 11,17 Interestingly, all these cases had benign features. Using the more sensitive array CGH method, a recent report demonstrated loss of heterozygosity for HRAS in chromosome band 11p15.5 and a less significant loss of the short arm of chromosome 16.…”
Section: Discussionmentioning
confidence: 93%
“…In addition to b-catenin mutations, an EWS/FLI-1 fusion transcript, t(11;22) (q24;q12), has been reported in a pediatric solid pseudopapillary neoplasm. 14 Subsequent papers showed that although FLI-1 is overexpressed in solid pseudopapillary neoplasms, 17 it is more likely due to a genetic alteration involving the long arm of chromosome 11 rather than an EWS-FLI-1 transcript. 20 Interestingly, two of our patients showed loss of 11q22.3, and one showed a gain at 11q13.5-q14, suggesting a role for changes in chromosome 11q during the development of solid pseudopapillary neoplasms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 The observed changes are not associated with gross chromosomal aberrations of this region, because such alterations were ruled out by comparative genomic hybridization of solid pseudopapillary neoplasms. 28 However, despite the absence of gross chromosome abnormalities, this chromosomal area seems to be vulnerable to distinct genetic changes in solid pseudopapillary neoplasms, because it harbors a number of genes whose proteins are frequently found to be overexpressed. These proteins include cyclin D1, FLI-1, progesterone receptor and CD56.…”
Section: Discussionmentioning
confidence: 99%
“…Microscopically, the tumor cells in 'solid' areas are uniform, arranged in sheets and cords around fibrovascular septa; whereas those in 'pseudopapillary' areas show degenerative changes in the cells away from the vasculature. [4][5][6][7][8] Despite its characteristic microscopic appearance and recent studies of this type of tumor for molecular changes, 9 the immunophenotype of markers is not specific and does not define a line of differentiation corresponding to any normal pancreatic cell type.…”
mentioning
confidence: 99%